LabVIEW automatic control system - Aw, Nixon Han Wei (Nanyang Technological University, 2021)
With the recent development of quantum computers getting smart and faster, encryptions are no longer as secure as before. Typical secret key cryptography will soon be susceptible to hacking with technology expansion and development. How trustworthy are the current encryptions methods? Quantum cryptography has been widely observed to be the next cutting-edge technology that uses physics to improve encryption. However, the proposed theoretical model makes use of various ideal scenarios which often defers from real-life implementation. To demonstrate the practicality of an MDI-QKD set-up, a proof-of-principal demonstration is performed. In this project, a LabVIEW control system is implemented, that will control series of instruments automatically to assist the signal generation, signal manipulation, and data acquisition of a MDI-QKD set up.